Impact of augmented reality on high school students’ motivation and understanding of acid-base titration concepts - Kartini, Ketut Sepdyana; Yusa, I Made Marthana; Adnyana, I Nyoman Widhi; Putra, I Nyoman Tri Anindia (Edelweiss Applied Science and Technology, 2024)
The integration of Augmented Reality (AR) in chemistry education, particularly in acid-base titration, offers an interactive approach that can improve students’ understanding. This study aimed to assess the effectiveness of AR in enhancing learning outcomes for tenth-grade students at SMA Negeri 4 Denpasar, while also evaluating the user experience through the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). A total of 60 students participated in AR-based learning, and the evaluation focused on changes in learning outcomes before and after using AR. The SUS was used to measure system usability, while the UEQ assessed user experience in terms of attractiveness, Perspicuity, efficiency, stimulation, and novelty. Results showed a significant improvement in student understanding, with an average test score increase of 25%. The SUS yielded a high usability score of 85, indicating that the AR system was easy to use. Additionally, the UEQ highlighted a positive user experience, particularly in stimulation and attractiveness, both rated "excellent." These findings suggest that AR not only improves learning outcomes but also provides an engaging and motivating learning experience.